Status of surface electromyography assessment as part of clinical gait analysis in the management of patients with cerebral palsy - Outcomes of a Delphi process - Reisig, Robert; Alexander, Nathalie; Armand, Stéphane; Barton, Gabor J.; Böhm, Harald; Boulay, Christophe; Brunner, Reinald; Castagna, Anna; Davoudi, Mehrdad; Desailly, Eric; Desloovere, Kaat; Dussa, Chakravarthy; et al. (Gait & posture, 2025)
Background - The assessment of gait disorders in patients with neuromotor conditions, such as cerebral palsy (CP), has been a focus of clinical and research attention, with electromyography (EMG) offering a nuanced understanding of neurological and neuromuscular disorders. However, the interpretation of EMG data in the context of gait analysis remains challenging due to the complexity of neuromotor dynamics and variability in assessment methodologies. - Research question - To which consensus can we get in a group of experts in the fields of neurological and neuromuscular disorders, biomechanics, and clinical gait analysis to establish standardized protocols and a common language for the measurement and analysis of EMG data in gait disorders, particularly in people living with CP? - Methods - A three-round Delphi process was conducted from February to September 2023 to gather opinions of 53 experts on the use of surface EMG data during gait in the context of CP. The surveys were conducted using the tool 'SoSci Survey' with a focus on free-text answers. - Results - The experts agreed on the usefulness of EMG data, but a consensus on specific clinical decisions involving EMG could not be reached. Additionally, the study provides a terminological framework for EMG evaluation during gait and a comprehensive list of practical problems and solutions, when evaluating EMG data. The study indicates that, despite a general community consensus on the ideal approaches to data processing and evaluation, these methods are not commonly implemented in a standardized manner. Both raw and enveloped data are widely used in clinical routines, however, the protocol for generating normative data lacks consistency across gait laboratories. - Significance - The study suggests that while there may be differences in the way EMG data is analyzed, there is a shared understanding of the key features that are relevant for gait analysis.